Literature Review: 3D Print on Design Thinking in The Design Process - Riono Aulia Abdullah (Universitas Pendidikan Indonesia (UPI), 2022)
Technological advances in additive manufacturing technology have been growing, one of which in rapid prototype, making prototipe with use technology is three-dimensional (3D) printing, which works by melting thermoplastic material in the making of a model or prototype. The materials used are Polylactic Acid (PLA) and Acrylonitrile Butadiene Styrene (ABS) which are molded by melting by heating the nozel according to the melting point and flowing in layers to form an object or objects. Design thinking is a method with a solution-based approach to solving a problem, with an iterative process to understand users, challenge an assumption, redefine the problem in an effort to identify strategies and alternative solutions to a problem, especially in the design process. Design thinking has five steps in the process, empathize, define, ideate, prototipe and test. This literature review aims to see the influence of the pengerjaan prototipe process in the design thinking method using 3d printing in the design process. The method used in this paper is to use descriptive qualitative research methods by analyzing the existing literature. So it can be concluded that the use of 3d printing in the design thinking method can be a new way of making prototipe in the design process.